Factors determining the development of intelligent transport systems - Okunevičiūtė Neverauskienė, Laima; Novikova, Marta; Kazlauskienė, Eglė (Business, Management and Economics Engineering, 2021)
Purpose – foreign and Lithuanian researchers analyse the benefits of ITS (Intelligent transport systems) application and development opportunities in various aspects. Due to the rapid development of technology, most authors emphasise the need for new or at least repeated research on intelligent transport systems ITS. The aim of this article is to evaluate the factors determining the development of ITS after theoretical substantiation. Research methodology – the primary data was collected from the following databases: Eurostat, OECD, World Bank. This study uses the analysis of scientific literature, expert survey, multicriteria assessment (SAW and COPRAS methods). Findings – the results of this article indicate which factors determine the development of ITS the most: investments, the aim to increase road safety, well-developed infrastructure. It also identifies which of the chosen for analaysis countries has the greatest potential for developing of ITS – Germany. Research limitations – firstly, due to the lack of statistics only eight countries are included and the period of analysis is only two years. Another limitation is that experts from only two countries completed the survey. Practical implications – research on the development of ITS is carried out in order to analyse the country that has the biggest opportunity to develop ITS and the factors affecting the mentioned development. The results can be beneficial for ministries of transport in different countries for planning the application of ITS. Originality/Value – current study contributes to the existing literature by examining the specific factors affecting the development of ITS that were not analysed earlier. This article differs from others as includes some Northern ,Western European and Baltic countries. Findings can be used by government in planning the installation of ITS to get the maximum benefit from it.